Research cooperation within and across regional boundaries. Does innovation policy add anything? - Alberto Marzucchi; Davide Antonioli; Sandro Montresor (European Commission, Joint Research Centre (JRC), 2012)
The paper aims to show how policy makers can stimulate firms' cooperation with research organisations in innovation. We argue that the administration of an R&D subsidy can be effective. Furthermore, this should be more so for extra-regional than intra-regional cooperation. The firms' propensity to extend cooperation across the region is assumed to increase with the amount of support. However, the support must overcome a threshold, for firms to cover the fixed costs of distant interactions. These research hypotheses are tested with respect to a sample of firms in a region of Italy. Propensity score matching is applied to identify the impact of the subsidy receipt. A generalised propensity score technique is employed to investigate the effect of an increasing amount of support. All the hypotheses are not rejected. Firms' cooperation is policy sensitive, but the size of the support is crucial for its effects.
Keywords: O32; O38; R11; R58; 330; Industry-Research Cooperation; Regional Innovation Systems; Behavioural Additionality